Askarova A.S., Mazhrenova N.R., Nugymanova A.O., Ermaganbetova S.D. Development of system scientifc and practical approach to decrease in anthropogenous load of the air basin of the city of Almaty: Al-Farabi Kazakh national university, Almaty, Kazakhstan (Eurasian Journal of Ecology, 2018)
The level of development of any country can be seen as three majorinterrelated factors: social, economic and environmental. It should be noted that the state should pay equal attention to, and provide equal supportto these areas without a priority one at the expense of others. This balancewill help to ensure a balanced development of any country. Decisions andactions aimed at protecting the environment should be based on a scientific basis and be based on objective indicators. In this article we are specified goals of modern science in the field of environmental protection studies, implemented in Kazakhstan. System Analysis Research has shown thatshould be paid more attention to an entirely new high-efficiency activitiesfor studying, reproduction and rational use of natural resources, technology, rehabilitation of the environment from the effects of anthropogenicinfluences, standardization, certification and metrology in environmentalmanagement, and the development of regulatory requirements.Key words: comprehensive pollution index, environmental metrology,maximum and single emissions, program complex «ERA-Air».